Experimental studies on a novel roll-to-roll powder hot embossing for large-area fabrication of micropyramid arrays on polymers. (8th May 2018) - Yi, Peiyun; Deng, Yujun; Shu, Yunyi; Peng, Linfa
Abstract: Roll-to-roll (R2R) hot embossing is regarded as a cost-effective replication technology to fabricate microstructures on polymer films. However, the characteristics of continuous and fast forming for the R2R hot embossing process limits material flow during the filling stage and results in significant springback during the demolding stage. To resolve this issue, this study proposed a novel R2R powder hot embossing process, which combines the merits of the continuous fabrication of R2R hot embossing and near-net-shape forming of powder sintering and also decreases the whole cycle of the fabrication from films to microstructures. First, the relation between the molten layer thickness and processing parameters was discussed and an analytical model was established to predict the feed of the polymeric powder during R2R powder hot embossing. Then, with the use of a micro-pyramid array mold, the impact of the process parameters including mold temperature, feeding speed and applied force on the geometrical dimension of the patterned microstructures was discussed. Last, based on the response surface analysis, a process window, in terms of the mold temperature of 132 °C –145 °C, feeding speed of 0.1–1.4 m min −1 and applied force of 15–50 kgf was determined for the continuous fabrication of completely-filled micropyramid arrays with the R2R powder hot embossing process. This research demonstrated the feasibility and superiority of the proposed R2R powder hot embossing process in continuously fabricating micropatterned structures on polymeric films.